Analisis Pelaksanaan Penilaian Kinerja Karyawan Pada PT Deco 100 Supermarket Indrapura - Sianipar, Christin Natalia; Nursaimatussaddiya, Nursaimatussaddiya; Suhadinda, Deby (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2023)
This study aims to analyze the implementation of employee performance appraisal at PT. Deco 100 supermarket Indrapura. The type and approach of the research is field research with a qualitative approach. Data collection techniques were obtained through observation, interviews and documentation. Based on the research and discussion, it can be concluded that the application of assessment to improve the performance of the employees of Deco 100 supermarket Indrapura has been done well. This is to encourage companies to prepare good quality and competent employees. The impact of employee performance appraisal is positive and negative. The positive impact is an increase in better work motivation, an evaluation according to the work standards that have been carried out, there is also feedback on past performance in the form of bonuses. Meanwhile, the negative impact is the imposition of a warning letter, not getting a reward and being able to stop working when making a fatal mistake